Personal and parents' life stories in patients with borderline personality disorder. Issue 3 (26th February 2019) - Lind, Majse; Thomsen, Dorthe Kirkegaard; Bøye, Rikke; Heinskou, Torben; Simonsen, Sebastian; Jørgensen, Carsten René
Abstract : Patients with borderline personality disorder (BPD) display disturbances in understanding self and others. We examined whether these disturbances extended to how patients described their personal and parents' life stories and to measures of identity, alexithymia, empathy, and emotional intelligence. Thirty BPD patients and 30 matched control participants described personal and parents' life stories and completed measures of identity disturbance, alexithymia, empathy, and emotional intelligence. Compared to the controls, patients with BPD described their personal and their parents' life stories more negatively and with fewer themes of agency and communion fulfillment. Patients and controls showed equally complex reasoning about their personal life stories, but patients displayed less complexity and more self‐other confusion, when reasoning about their parents' stories. Patients also differed from controls on identity disturbance, alexithymia, and empathy. The results suggest that patients' storied understanding of themselves and others are disturbed and should be taken into account to better understand BPD.